Perilaku Swamedikasi Masyarakat Wonosobo selama Pandemi Covid-19 - Rezha Nur Amalia; Eva Annisaa'; Ragil Setia Dianingati (Majalah Farmaseutik, 2022)
The COVID-19 pandemic has resulted in restrictions on health services. It is estimated that there is concern about being infected when going to a health care facility that can influence people's behavior to do self-medication. This study aims to determine the behavior of self-medication in the Wonosobo community during the Covid-19 pandemic and the factors that influence it. This research is an observational descriptive study with an online survey technique using a questionnaire and using 107 samples with certain criteria obtained using a purposive sampling technique. The majority of respondents did self-medication 1-2 times during the Covid-19 pandemic (67.3%). The reason for doing self-medication is because they used to do it before the pandemic (57%), and the most felt complaint was pain (16%). The majority of drugs consumed were antipyretic drugs (26%) and the majority had taken drugs that are legally allowed to be used for self-medication (96%). The majority of respondents buy drugs at pharmacies (92%) and if they do not recover, they will check with a doctor (59.8%). The results of the test of the relationship between self-medication behavior with factors of age, education, and knowledge (p <0.05). While the factors of employment, income, health facilities, ownership of health insurance, type of health insurance, and sources of information on drug selection had no significant effect (p>0.05). So it can be concluded that age, education, and knowledge affect self-medication behavior in the Wonosobo community during the Covid-19 pandemic.